Automated self-watering plant system: integrating sensors and IoT for optimal indoor plant care / Norhalida Othman ... [et al.] - Othman, Norhalida; Mohd Sabri, Muhammad Umar Aiman; Muhamad, Nur Amalina; Khairul Anuar, Noor Hafizah; Abdul Majid, Masmaria; Mat Saat, Ezril Hisham; Md Sin, Nor Diyana (UiTM Press, 2025)
Houseplants enhance indoor environments by improving aesthetics, boosting mood and creativity, and reducing air pollutants. However, maintaining houseplants requires regular watering and care, which can be challenging for individuals with demanding schedules. To address this issue, we developed an automated self-watering plant system that automates plant care through the integration of sensors and IoT technology. The system utilizes a Soil Moisture Sensor, a pH Level Sensor, and a DHT11 Temperature and Humidity Sensor, all connected to an Arduino UNO microcontroller, to continuously monitor soil moisture, pH levels, and environmental conditions. A small pump automates the watering process, delivering water as needed, while an LCD displays the measured pH levels. Additionally, IoT technology transmits real-time data from the Arduino to the owner's mobile phone via the ESP8266 module, allowing users to remotely monitor their plants’ conditions. This automated self-watering system offers an effective solution for plant enthusiasts seeking to maintain healthy plants with minimal effort.